Implementasi Manajemen Perpustakaan Sekolah Untuk Meningkatkan Minat Baca Siswa Kelas Atas SD Muhammadiyah 16 Surakarta Tahun Pelajaran 2016/2017 - Kurniawan, Wahyu; , Dra. Ratnasari Diah Utami, M.Si., M.Pd (2017)
The study aims to: (1) describe the implementation of the management of school library in order to increase reading interest for studenst in the upper-class SD Muhammadiyah Surakarta 16 in 2016/2017, (2) identify the obstacles faced in implementing the management of school library in increasing reading interest for students in the upper-class SD Muhammadiyah Surakarta 16 in 2016/2017, and (3) describe the interest increase efforts read students through school library management activities in students of upper-class SD Muhammadiyah Surakarta 16 in 2016/2017. This type of research is qualitative research. The technique of collecting data through observation, interviews, and documentation. The techniques of data analysis the form of an interactive model analysis Miles and Huberman. The validity or legality of the data using triangulation of sources and methods. The results of this study suggest that (1) the implementation of the management of school library in order to increase interest in reading students SD Muhammadiayh 16 Surakarta in 2016/2017, i.e. have been applying some elements of management that includes elements of planning , organizing, leading, and controlling), (2) obstacles faced in implementing the management of school library in increasing reading interest for student in the upper-class SD Muhammadiyah Surakarta 16 in 2016/2017 , that includes constraints of limited time in a primary against reading at library, the constraints of limited library services, the constraints of limited variety and number of library collection and a travelling library in the availability constraints against interest read, and (3) increase efforts read ing interest for students through school library management activities of upper-class SD Muhammadiyah 16 Surakarta in 2016/2017 i.e. namely instilling awareness in students in reading, provides an extensive library of materials, conditioning and reading.